Clinico-epidemiological study of neonatal seizures from a tertiary care hospital of Western Rajasthan, India - Verma, Suresh Kumar; Dabi, Jagdish Chand; Rawat, Sandeep; Dabi, Basanti (International Journal of Contemporary Pediatrics, 2019)
Background: Neonatal Seizures are frequent may be either symptoms of an underlying disorder and malfunction of the developing CNS or due to a primary epileptic condition. Their varied clinical presentations, delay in recognition and treatment results in poor neurological outcome. This study attempts to find out the clinical and etiologic profile of neonatal seizures and associated biochemical abnormalities in this geographical part of India. Methods: A hospital based prospective observational study undertaken in a tertiary care pediatric hospital of Medical College Jodhpur India, on 202 consecutive neonates who presented with seizures during period of one year. A detailed antenatal history and baseline characteristics of convulsing neonate at admission and clinical details of each seizure episode reported by the mother and subsequently observed by doctors on duty were recorded. Venous blood sample was analyzed as soon as possible for blood glucose, total serum calcium levels and electrolytes, before instituting any treatment. Data were managed on Microsoft Excel spreadsheet, and analysis was performed using SPSS version. Results: The overall frequency of neonatal seizures in our set up was recorded as 4.08%. Perinatal asphyxia with subsequent HIE was the most common (40.09%) cause of neonatal seizures while hypoglycemia was the most common metabolic cause (11.38%) observed specially in VLBW babies. Subtle seizures were the most common type (34.65%) and tonic seizures were the second most common (33.66%) type of seizures encountered. Hypocalcemia was the second commonest biochemical abnormality found in primary metabolic seizures. HIE, ICH and Hypoglycemia were the common seizure etiology in preterm neonates. Conclusions: Perinatal asphyxia and subsequent HIE was the commonest etiology with subtle, tonic and multifocal seizures being the commonest clinical types encountered. Hypoglycemia and hypocalcemia were the most frequent biochemical abnormality found.